The Influence of Brand Ambassador Iqbaal Ramadhan on Parental Decisions in the Digital Community of East Java Smart Parents in Choosing Ruangguru as a Children's Online Tutoring Media - Assalamah, Tuhfatul Mubarokah (Universitas Negeri Surabaya, 2020)
This study discusses the influence of Brand Ambassador Iqbaal Ramadhan on parents' decisions in the Smart Parents digital community in East Java in choosing Ruangguru as a medium for children's online tutoring. The object of this research is Ruangguru as an educational startup that was founded in 2014. While the subject of this study is the digital community Smart Parents, East Java, which brings parents' decisions in determining children's education. This study uses four VisCAP Brand Ambassador variables (Royan, 2004) namely Visibility, Credibility, Attraction, and Power. The approach in this study is a quantitative approach with a simple linear regression method. Data collection techniques using questionnaire instruments with saturated sample techniques. The sample in this study was the entire population of the Smart Parents digital community in East Java, amounting to 60 people. Based on the results of research that has been done, it is found that there is the influence of Brand Ambassador Iqbaal Ramadhan on the decisions of parents in the Smart Parents East Java digital community in choosing Ruangguru as a medium for online children's tutoring by 35.3% and Attraction variable has a significance value of 45% in influencing decisions parents. Keywords: Brand Ambassador, decision to choose, parents, Ruangguru